Analysis of Village Fund Allocation Management (ADD) in Village Development Efforts in Bontoala Village, Pallangga District, Gowa Regency - Asdar, Asdar; Jam’an, Andi; Pratiwi, Octaviani (Jurnal Ekonomi Balance, 2022)
The purpose of this study was to determine how the management of village fund allocation in Bontoala Village Pallangga District Gowa Regency. Data collection techniques in this study by observation interviews and documentation. The result of the researchfrom the analysis of village fund allocation management (ADD) in village development efforts in Bontoala Village, Pallagga District, Gowa Regency show that: 1). The Village Fund Allocation (ADD) palnning stage in bontoala village has implemented the principle of transparancy. 2). At the implamentation stage of the ADD, Bontoala Village carried out-self management because the village government also nedeed to improve the welfare of the community. 3). The accountability stage for village fund allocation (ADD) in bontoala village, both technically and administratively, is good, but still requires guidance from the sub-district government.